2019
DOI: 10.1186/s42409-019-0008-6
|View full text |Cite
|
Sign up to set email alerts
|

The short version of the Metacognitive Prospective Memory Inventory (MPMI-s): factor structure, reliability, validity, and reference data

Abstract: Prospective memory, the ability to remember to execute an intended action at the appropriate moment in the future, is frequently assessed with standardized questionnaires. Prospective-memory abilities strongly depend on the different strategies people use to remember their intentions. In this study, we introduce the short version of the Metacognitive Prospective Memory Inventory (MPMI-s) that allows for a quick assessment of individual differences in self-reported prospective-memory abilities as well as in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 39 publications
2
18
0
Order By: Relevance
“…Importantly, those who were more underconfident in their ability also showed a greater reminder bias, consistent with the metacognitive bias view. These results fall in line with previous findings that JOLs and strategy use correlate with PM task performance (Kuhlmann, 2019;Rummel et al, 2019;Schnitzspahn, Zeintl, et al, 2011;Susser & Mulligan, 2019), and suggest that people are aware in the benefit of offloading on performance and err on the side of caution, thus employing it more frequently than they actually need. One caveat to this interpretation was that this relation appeared to be task-specific, meaning that metacognitive bias on one task (e.g., 123 task) was not associated with a reminder bias on the other tasks (e.g., ABC and 321 tasks).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Importantly, those who were more underconfident in their ability also showed a greater reminder bias, consistent with the metacognitive bias view. These results fall in line with previous findings that JOLs and strategy use correlate with PM task performance (Kuhlmann, 2019;Rummel et al, 2019;Schnitzspahn, Zeintl, et al, 2011;Susser & Mulligan, 2019), and suggest that people are aware in the benefit of offloading on performance and err on the side of caution, thus employing it more frequently than they actually need. One caveat to this interpretation was that this relation appeared to be task-specific, meaning that metacognitive bias on one task (e.g., 123 task) was not associated with a reminder bias on the other tasks (e.g., ABC and 321 tasks).…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with this, studies have shown that people's global judgments of learning (JOLs) generally correlate with their performance on PM tasks (Meeks et al, 2007;Schnitzspahn, Zeintl, et al, 2011;Susser & Mulligan, 2019), although people are often underconfident in their predictions (Kuhlmann, 2019). Moreover, Rummel et al (2019) found that self-reported internal and external PM strategies used in naturalistic settings were positively associated with reported PM ability.…”
Section: Metacognitionmentioning
confidence: 87%
“…Metacognitive Prospective Memory Battery The questionnaire included only the seven "internal" items from the measure from Rummel et al (2019), asking about strategies for fulfilling intentions not involving external aids (e.g., "In my mind, I make a list of things that I still have to complete. ").…”
Section: Schizotypy-magical Ideation Scalementioning
confidence: 99%
“…Existing studies investigating perceived PM abilities measured with self-report questionnaires such as the Prospective and Retrospective Memory Questionnaire (PRMQ) and the short version of the Metacognitive Prospective Memory Inventory (MPMI-s) have found no age-related differences (Crawford et al, 2003) or small age variations (Rummel et al, 2019). However, Scarampi and Gilbert (2021) administered the MPMI-s at the end of a delayed-intention task and found that older adults reported higher PM abilities than their younger counterparts.…”
Section: Metacognition Prospective Memory and Agingmentioning
confidence: 99%